Pilot Study: Characterizing Successful Beginning Reading in Indonesian - Harwintha Yuhria Anjarningsih (Journal of English Language and Culture, 2020)
The investigation reported in this article aims to point out how the lexical and sub-lexical route are employed in normal beginning reading in Bahasa Indonesia (Indonesian) and to identify reading performance that may suggest the occurrence of impaired reading in Bahasa Indonesia which is possibly displayed by the children with the lowest reading performance. Ten typical developing third-grade students participated in the study. Error pattems of those ten students are analysed for the error analysis and for the analysis on the relationship between psycholinguistic variables and reading perforrnance. Five of those students were recorded during the reading part and the data were used in the latency analysis. The prelirninary findings reported here seem to show that beginning reading in Bahasa Indonesia is characterised by the utilization of the sub-lexical route and more skilled reading by lexical route. The development of the lexical route depends on the development of the sublexical route which is influenced by the complexity of the Grapheme Phoneme Correspondence. The lexical route for words with simple graphemes is developed first, the lexical route for words with consonant clusters are developed later. The last to be developed is the lexical route for words with digraphi. Furthermore, Late AoA, imageability, syllable number, and resemblance to words influence the lexical processing of the stimuli in the test. Impaired reading seems to be characterised by less developed sub-lexical route as evidenced by difliculties with words containing consonant clusters and digraphs and longer latencies for reading aloud words and pseudowords.Keywords: psycholinguistics, reading performance